The Choice of Candidates in Survival Markers Based on Coordinated Gene Expression in Renal Cancer - Apanovich, Natalya; Apanovich, Pavel; Mansorunov, Danzan; Kuzevanova, Anna; Matveev, Vsevolod; Karpukhin, Alexander (Frontiers in Oncology, 2021)
Identification and expression investigation of essential for the ccRCC development genes may shed light on progression mechanisms and contribute to creating prognostic markers that was the aim of our study. We used RT-PCR to study the expression of 20 genes, preliminary selected as differentially expressed in ccRCC, on 68 paired tumor - norma samples. When ccRCC progressed, seven genes reduced the initially increased expression. The other part of the genes did not significantly change the expression level and was associated mainly with metabolic and inflammatory processes. The first group included CA9, NDUFA4L2, EGLN3, BHLHE41, VWF, IGFBP3, and ANGPTL4, which coordinately decreased expression levels during tumor progression. This coordination and gene function is related to the needs of tumor development at different stages. In particular, the high correlation coefficient of EGLN3 and NDUFA4L2 expression may indicate the importance of coordinated regulation of glycolysis and mitochondrial metabolism. A panel of CA9, EGLN3, BHLHE41, and VWF allows predicting ccRCC patient survival for more than 3.5 years with a probability close to 90%. Thus, for the first time, a coordinated change in the gene group expression during ccRCC progression was detected and a new panel of markers for individual survival prognosis was found.